An investigation into global distribution systems in the crop protection industry and the development of distribution system managment model for particular application in South Africa and Australia - Schreuder, F. A. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2002.